Comparative Effectiveness of Recurrent Laryngeal Nerve Monitoring Techniques in Pediatric Surgery. (25th August 2021) - Lawlor, Claire M.; Meisner, Jay; Jennings, Russell W.; Zendejas, Benjamin; Choi, Sukgi S.
Abstract : Objectives/Hypothesis: The recurrent laryngeal nerve (RLN) is at risk during pediatric cervical, thoracic, and cardiac surgery. We aim to determine the feasibility and effectiveness of RLN monitoring techniques in all pediatric patients. Study Design: Retrospective case series. Methods: Retrospective review of patients/procedures with RLN(s) at risk and RLN monitoring at Boston Children's Hospital July 2019–October 2020. Primary outcomes: pre/postoperative vocal fold mobility by awake flexible fiberoptic laryngoscopy (FFL). Results: One hundred one patients (median [interquartile range, IQR] age 14.6 months [4.6–49.7 months], weight 10 kg [5.2–16.2 kg]) underwent 122 procedures with RLN(s) at risk. RLN monitoring attempted 111 cases, successful 96 (84%). Surgical indications: esophageal atresia/tracheoesophageal fistula, and tracheobronchomalacia. Sixty‐two (56%) procedures in reoperative field. Median follow‐up 112 days (IQR 41–230). Pre/postoperative FFL performed 84 procedures (69%), 19 new postoperative RLN injuries (16%), median age 12 months, reoperative fields 11 (18%). Prass probes: 34 cases (28 successful, 82%), 6 injuries (18%), age 12.2 (5.8–23.6) months. Dragonfly electrodes: 45 cases (37 successful, 82%), 8 injuries (18%), age 7.5 (3.8–19) months. Nerve integrity monitoring (NIM) integrated electrode endotracheal tube: 33 cases (33 successful, 100%), 5 injuries (15%), age 90 (58.8–136.7) months. Automatic periodic stimulation (APS): 16 cases, 13 successful (81%), four injuries (25%), age 7.2 (5.3–20.6) months. NIM RLN monitoring is significantly more successful than Prass, Dragonfly (95%CI −0.3 to 0.02, P  = .02; and 95%CI 0.05–0.31, P  = .008). Rates of injury are not different between types of RLN monitoring ( P  = .94), with APS use ( P  = .47), or with monitoring success (95%CI −0.36 to 0.09, P  = .28). Conclusions: RLN monitoring is feasible in pediatric patients of all ages. Although NIM type RLN monitoring success is superior, all forms offer similar rates of nerve protection. Level of Evidence: 3 Laryngoscope, 132:889–894, 2022